Anisakidae Skrjabin & Karokhin, 1945 and Raphidascarididae Hartwich, 1954 nematodes in lutjanidae (pisces: perciformes) from the Brazilian Northeast Coast - Alves,A. M. (2020)
Abstract The present study aimed at describing and evaluating the fauna of Anisakidae and Raphidacarididae nematodes of lutjanid fish (snappers) from the Brazilian northeastern coast unloaded at the city of Aracaju, capital of the State of Sergipe. A total of 186 lutjanids of 5 different species were analyzed including 69 Lutjanus analis, 51 L. vivanus , 29 Ocyurus chrysurus, 23 L. synagris, and 14 L. jocu. Nematode specimens found in the viscera of these fish were clarified with lactophenol. Illustrations of each of these specimens were prepared to help identify these samples and compose their taxonomic description and classification. At necropsy, 3,183 nematodes belonging to two families were collected from fish viscera which included the following: Anisakidae: Anisakis, Terranova , Contracaecum, and Goezia; Raphidascarididae: Raphidascaris (Ichthyascaris) and Hysterothylacium . A total of six genera of nematodes were found at postmortem examination of which adult worms of only three genera (Goezia, Raphidascaris and Hysterothylacium) were detected in the fish examined. Larvae of Terranova sp. were found only in the musculature of O. chrysurus . Most of the nematode larvae were present in the mesentery and organs of the fish necropsied. Therefore, the zoonotic potential of these nematodes cannot be ruled out. There was a significant negative correlation between the intensity of parasitism by anisakids and the total body length of O. chrysurus; the intensity of parasitism was greater in smaller and shortef fish. There was a significant positive correlation between the abundance of these parasites and the length of L. synagris; the presence of these parasites increased according to the fish’s body length. To the authors’ knowledge, these are the first records of Raphidascaris (Ichthyascaris ) sp. and Hysterothylacium sp. in L. vivanus , of Terranova sp. in O. chrysurus and L. jocu, and of Goezia sp. in L. analis. These novel findings add the Brazilian northeast coast and the State of Sergipe in the geographic distribution of these parasites in the country.